PRODUKTIVITAS HIJAUAN YANG DITANAM PADA NAUNGAN POHON KELAPA SAWIT DENGAN TANAMAN CAMPURAN - Wijaya, Agung Kusuma; Muhtarudin, Muhtarudin; Liman, Liman; Antika, Cloudia; Febriana, Dini (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2018)
This research intended to determine the effect of palm oil tree shade and mixed planting on grass and leguminous on productivity. This research has been done on March—June 2018 in Tanjung Agung Area, Katibung District, Kalianda, South Lampung. This research used Completely Randomized Design (CRD) with split plot design method. The treatment was implemented in this research is (1) shading, consist of two levels, which are N0 (without shade) and N1 (palm oil tree shade) and (2) mixed plant species, consist of two variations; which is A1 (elephant grass and purple bush bean) and A2 (dwarf elephant grass and purple bush bean). The data which obtained were analyzed by analysis of variance on 5% significant level, then if the result significantly difference, it were analyzed with Duncan Multiple Range Test (DMRT). The results showed that palm oil shading has not significant effect on grass productivity. there is an interaction between the type of grass and oil palm shade on the number of elephant grass and odot grass tillers. The dry matter of grass on mixed planting on land without shade was significantly different with dry matter of grass on mixed planting in palm oil shade. However, it has tendency to increase organic matter of grasss on palm oil shade. Keywords: Palm Oil Shade, Elephant Grass, Dwarf Elephant Grass, Mixing Grass, Productivity